Assessment of respiratory symptoms and pulmonary functions in rickshaw drivers in Biratnagar, Nepal - Koirala, Puru; Mehta, Ram Kumar; Parajuli, Surya B. (Journal of Karnali Academy of Health Sciences, 2024)
Background: Ambient air pollution is a cause of chronic respiratory diseases. Nepal has an increasing burden of respiratory morbidities, and Biratnagar city has a poor air quality index. Rickshaw drivers are exposed to ambient pollutants for long durations. The study aimed to determine the prevalence of respiratory symptoms in rickshaw drivers of Biratnagar and to  measure their pulmonary function.Methods: A cross-sectional study was conducted from January 2022 to January 2023. A structured questionnaire recorded data on socio-demographic variables and respiratory symptoms. Hand-held portable spirometer EasyOne® Air documented lung function parameters. Data was presented as descriptive statistics.Results: There were 348 rickshaw drivers in Biratnagar enrolled in the study, all were male, with a mean age of 36.13 (±11.07) years and a mean duration of occupation of 5.38 (±3.61) years. Phlegm was present in 102 (29.31%), 78 (22.41%) had cough, 72 (20.69%) noisy breathing, and 54 (15.52%) dyspnea. There were 189 (54.31%) with impaired lung functions. Restrictive impairment was present in 131 (37.64%), mixed disorder in 38 (10.92%), and obstructive impairment in 20 (5.75) drivers. Our descriptive data suggested that rickshaw drivers who had longer duration of occupation had more impairment of pulmonary functions.Conclusion: Phlegm production, cough, noisy breathing and dyspnea were common respiratory symptoms in rickshaw drivers in Biratnagar. Drivers who had longer duration of occupation demonstrated more pulmonary dysfunction. Rickshaw drivers are at risk for chronic respiratory disease and need proper education on preventive strategies and regular screening for lung function outcomes.